Machining Operations on Messassa Wood - Narciso Fernando Bila; Rosilani Trianoski; Márcio P. Da Rocha; José Reinaldo Moreira da Silva; Setsuo Iwakiri; Andrade F. Egas; Alberto F. Mussana (Masyarakat Peneliti Kayu Indonesia, 2020)
This study aimed to evaluate the effect of machining operations on the surface quality of the messassa wood (Brachystegia spiciformis and Julbernadia globiflora) for use in the furniture industry. The wood cames from Mozambican Miombo Woodland. The following machining operations were performed: planing, shaping, milling, tearing and boring based on technical standard. The wood had a surface quality approval rating above 70% in all tested machining operations. A perfect surface quality was obtained with a feed speed of 6 m.min-1 in planing. Brachystegia spiciformis had easy workability and extremely well performance compared to Julbernadia globiflora. Nevertheless, both wood species have great potential for use in higher value-added products such as furniture and frame production.